Highlights of the 2020 American Heart Association : Guidelines for CPR and ECC / American Heart Association - American Heart Association
These Highlights summarize the key issues and changes in the 2020 American Heart Association (AHA) Guidelines for Cardiopulmonary Resuscitation (CPR) and Emergency Cardiovascular Care (ECC). The 2020 Guidelines are a comprehensive revision of the AHA’s guidelines for adult, pediatric, neonatal, resuscitation education science, and systems of care topics. They have been developed for resuscitation providers and AHA instructors to focus on the resuscitation science and guidelines recommendations that are most significant or controversial, or those that will result in changes in resuscitation training and practice, and to provide the rationale for the recommendations.